Serpentine supravenous hyperpigmentation (SSH) in nasopharyngeal carcinoma patient on docetaxel and carboplatin chemotherapy: a case report - Sutiawan, Indry Salonika; Puspawati, Ni Made Dwi; Martalova AJ, Adelia; Setyono, Alfred; Devi, Putu Akopita; Setyawati, Ni Kadek (Published by Universitas Gadjah Mada, 2024)
Serpentine supravenous hyperpigmentation (SSH) is a rare but unique side effect of intravenous anticancer. It manifests as linear hyperpigmentation eruption on the skin that radiates along the superficial vein accompanied by mild pain and/or itch. This SSH does not cause systemic alterations, however, most patients complained about its cosmetic effects. The diagnosis of SSH can be made clinically, although histopathological examinations can aid in excluding differential diagnoses. We reported a case of SSH found in a nasopharyngeal cancer patient during docetaxel and carboplatin chemotherapy. It is a potentially alarming interface dermatitis that is not lot reported in the literature. It was reported, the patient tolerated the second and third cycles well with less severe side effects when premedicated with 250 mL NaCl 0.9% bolus intravenously before and after chemotherapy sessions, 10 mg cetirizine every 24 hr orally, and desoximetasone cream 0.25% every 12 hr topically added.